Fungsionalisasi Limbah Cair Industri Tahu Tradisional PRIMKOPTI Jakarta Barat Sebagai Media Tumbuh Spirulina platensis - Nita Noriko (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2011)
Tofu industry produce organic waste in the form of liquid and solid. But, most of the industry cast away its waste to the surroundings directly without any processes before and contaminate the environment. One way out to solve this problem is by functionalizing the liquid waste as growth media of Spirulina platensis. In this research, exemic culture method with independent microalgae is used. Based on the result of the research, the optimal  growth of Spirulina platensis  if  cultured in 10% concentration of liquid waste with 4:6 comparison (400 ml Spirulina platensis : 600 ml tofu liquid waste). It is indicated by green color intensity of Spirulina platensis.